The Personal Identification by Means of Cheiloscopy among People of North India - Mukul Chopra (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Personal identification is becoming increasingly important not only in legal medicine but alsoin criminal investigation, identification and in Genetic Research. The grooves present on the lips are uniquefor every person. Cheiloscopy is a forensic investigation technique that deals with the identification basedon lip traces.The aim of this study was to assess the specific lip print pattern for personal identification, itsuniqueness among males and females and the reliability of the technique in suspect identification at thecrime site.Materials and Methods: The study sample comprised 200 individuals (100 males and 100 females) agedbetween 10 and 50 years; dark?colored lipstick was applied uniformly on the lips and clear impressions ofthe lips were taken on the bond paper. The scanned lip-print image studied using Microsoft office picturemanager. Fingerprints were analyzed by following the classification given by Suzuki and Tsuchihashi.Chi?square test and p-value of the samples were calculated.Results: The study revealed that the lip print patterns for each individual were unique and there was nopeculiar pattern distribution among male and female subjects.Conclusion: Cheiloscopy is analogous to fingerprint analysis and can be used as a tool for individualidentification along with dermatoglyphics. It can also be used as an aid in forensic sex determination.